Phylogenomic Analysis of Campylobacter fetus Reveals a Clonal Structure of Insertion Element ISCfe1 Positive Genomes - Abdel-Glil, Mostafa Y.; Hotzel, Helmut; Tomaso, Herbert; Linde, Jörg (Frontiers in Microbiology, 2020)
Subspecies of the species Campylobacter fetus are associated with specific host niches including mammals and reptiles. C. fetus subsp. fetus is a zoonotic pathogen infecting humans. Infections can vary from an acute intestinal illness to severe systemic infections, with sheep and cattle as major reservoirs. In contrast, C. fetus subsp. venerealis causes bovine genital campylobacteriosis, which leads to abortion in cattle and a high economic burden for the farmers. Therefore, high-quality molecular subtyping is indispensable for interventional epidemiology. We used whole-genome sequencing (WGS) data of 283 Campylobacter fetus strains from 18 countries and compared several methods for Campylobacter fetus subtyping, including WGS, multilocus sequence typing, PCR assays, and the presence of the insertion element ISCfe1. We identified a highly clonal clade (designated as clade 1) that harbors the insertion sequence ISCfe1. The presence of this insertion sequence is an essential diagnostic tool for the identification of the subspecies Campylobacter fetus subsp. venerealis, serving as a target for several PCR assays. However, we have found a high sequence variability for the ISCfe1 besides the presence of ISCfe1-paralogues in certain other genomes (n=7) which may cause incorrect diagnostic results. Clade 1 seems to be the cattle-specific clade of this species. We propose that only this clade might be designated as Campylobacter fetus subsp. venerealis as it harbors the ISCfe1 marker sequence, which is a major target for molecular methods currently used for Campylobacter fetus subspecies identification. Fostering this proposal, we defined eleven stable nucleotide markers specific for this clade. Additionally, we developed a bioinformatics toolbox for the fast identification of this clade based on WGS data. In conclusion, our results demonstrate that WGS can be used for Campylobacter fetus subtyping overcoming limitations of current PCR and MLST protocols.